Método de eletrorresistividade aplicado ao estudo do contorno estrutural da região do Domo de Piratininga-SP - Ferreira, Vinicius Zoratti [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The study area covers a region to the south of the municipality of Bauru, represented by the Piratininga Dome. In the center of this structural high, outcrop Permian (Pirambóia Formation) and Triassic (Pirambóia Formation), in contrast to the Cretaceous formations (Bauru Group), in the vicinity of the area. In the 1980s, several studies and research were developed on the Piratininga Dome, since this one shows absence of the Serra Geral formation, being conducive to a hydrocarbon trap. The general objective of this work is structural contour mapping and interaction between the anomaly of the basement and the missing units. The geophysical data of Vertical Electrical Survey (VES) were processed and used for mapping. Several maps were elaborated for an interpretation of the structural high, mainly the structural map of the Serra Geral Formation and the crystalline basement. The anomaly in the crystalline basement of the Paraná Basin is the fundamental factor for the irregularity of the Serra Geral Formation and the cause of the absence of this unit

A área de estudo abrange a região ao Sul do município de Bauru, representado pelo Domo de Piratininga. No centro desse alto estrutural afloram rochas do Permiano (Grupo Passa Dois) e do Triássico (Formação Pirambóia), em contraste com as formações do Cretáceo (Grupo Bauru) que estão nos arredores da área. Na década de 80 ocorreram diversos estudos e pesquisas no Domo de Piratininga, pois este apresenta ausência da Formação Serra Geral, o que seria propício para a formação de uma armadilha de hidrocarbonetos. O objetivo geral deste trabalho é a elaboração de mapas de contorno estrutural e a interação entre a anomalia do embasamento com as unidades ausentes. Os dados geofísicos de Sondagem Elétrica Vertical (SEV's) foram processados e utilizados para a elaboração dos mapas. Foram elaborado diversos mapas para a interpretação do alto estrutural, principalmente o mapa de contorno estrutural da Formação Serra Geral e do embasamento cristalino. A anomalia existente no embasamento cristalino da Bacia do Paraná é o fator fundamental para a irregularidade da Formação Serra Geral e a causa da ausência dessa unidade
Keywords: Geofisica; Hidrocarbonetos; Mapeamento geologico; Bauru (SP)